Evaluating polytrauma patient outcomes and their correlation with trauma severity - Velonas, Georgios; Linardatou, Vasiliki; Koutete, Dimitra; Alevizopoulos, Nektarios; Paraskevi, Despoina; Dritsas, Spyridon; Papadopoulos, Athanasios; Magkoutas, Georgios; Kalogianni, Antonia; Marvaki, Christina (Health & Research Journal, 2025)
Background: Worldwide, injuries are the cause of death for 4.4 million people per year. Identifying clinical indicators that reliably correlate with the severity and outcomes of polytrauma patients can play a crucial role in improving their care. The present study aimed to assess the outcome of polytrauma patients and relate it to the severity of the trauma. Method and Material: This is a prospective observational study of 65 polytrauma patients (45♂) who came to the ER, aged over 16, with multiple injuries, and were admitted to the hospital. Data were collected through a structured recording form, including patient clinical data and outcome scales for life expectancy and outcome assessment (TRISS, APACHE II, Marshall CT Scan Grade, GOS-E). Results: The average age of those with multiple injuries was 48.95 years (SD 19.91). The main mechanism of injury was blunt trauma (98.5%). The most common cause of treatment was traffic accidents (58.5%). The shortest median length of stay in the emergency room was 200’. The most common complications were transfusions (18.1%), sepsis (16.9%) and pneumonia (12.8%). The median length of hospital stay was 30 days, with 46.1% of patients recovered and 41.6% disabled. Trauma scores were analysed for the relationship between length of stay and outcome. The hazard function was statistically significant (χ²(3) = 24.784, p < 0.001), with the TRISS scale identified as a significant predictor (p = 0.002, OR = 0.96). Each increase in the TRISS scale reduces the risk of death by 4%. The model, including the TRISS scale, patient waiting time in the emergency department (ED), and oxygen saturation in the ED, was also statistically significant (χ²(3) = 20.029, p < 0.001), confirming the TRISS scale confirmed as a significant predictor (p = 0.002, OR = 0.96). Conclusions: In patients with polytrauma, the TRISS scale was shown to be a valid predictor of results. Its use in clinical practice can enhance patient care and direct early action.